A Comparative Study of Standards-Based Curriculum among Public and Private Junior High School Students’ Achievement in Mathematics in Ghana - Suraj Nurideen; Francis Mwinlaanaa; Henry Manmana Kuubar; Abdul-Mumin Al-hasssan; Yarhands Dissou Arthur (EDUPEDIA Publisher, 2026)
Purpose – To compare the effectiveness of Standards-Based Curriculum (SBC) implementation in Ghanaian public versus private junior high schools (JHS). This study compares the effectiveness of SBC implementation in these sectors. To synthesize insights towards improving SBC implementation with an emphasis on equity, teacher empowerment, and infrastructure. Methodology – Qualitative interviews were conducted with six mathematics teachers and five students. Interviews gathered participants' opinions, perceptions, and personal experiences regarding SBC implementation. A small sample of six (6) mathematics teachers and five (5) students from public and private JHS settings. Findings – Interview results